Cinco crônicas de Charles Dickens em Sketches by Boz: um retrato do cotidiano londrino, no século XIX, através do humor - Gomes, Ana Lívia Verona Bernardes (2017)
The Sketches of Charles Dickens in his first book, Sketches by Boz (1836) present several themes, which through humor and characters showed real life, routine of the streets and workers in London. Dickens drew a portrait of puritan and hypocritical middle class Victorian bourgeoisie. Eagleton (2003), Hunter (2007), Phyhönen (2007), Ryan (2007) Rollemberg (2003), Watt (1990) and others studies based the discussion about literature concepts and literary genres boundaries; the narrative structure; and the influence of historic, cultural and social aspects in the narrative. English Literature studies the Literary Sketches or just Sketches as types of Short Stories or Short fiction, a literary theoric field in expansion that does not agree in terms of taxonomy, since there are several others expressions to Short Story under discussion. Hunter (2007) argues that the idea of art and creative action in Short Story allow that between the text brevity have complexity, several forms and narratological structures, which in Dickens's text resulted in a portrait of London, in the 1800s. Therefore, Dicken’s sketches describe in details everyday situations, draw a graphic representation of characters and scenes through the humor, which is used as a social criticism to the values of the Victorian period. The Sketches: "The Great Winglebury Duel"; "Omnibuses"; "The pawnbroker's shop"; "The Four Sisters"; "The Misplaced Attachment of Mr. John Dounce" and their translation into Brazilian Portuguese illustrate the comparison of the short story – sketches – with Brazilian chronicle, as well as stand out the Dickens style in his whole book Sketches by Boz.